Influence of RGD grafting on biocompatibility of oxidized cellulose scaffold. (December 2013) - Mahmoodi, Mozaffar; Hossainalipour, Seyyed Mohammad; Naimi-Jamal, Mohammad Reza; Samani, Saeed; Samadikuchaksaraei, Ali; Rezaie, Hamid Reza
Abstract Cellulose powder was oxidized by NO2 gas and the porous scaffold was fabricated by dry pressing. RGD peptide was immobilized on the surface of scaffold by grafting to make a hybrid scaffold. The hybrid scaffold was characterized by SEM and FTIR and its biocompatibility was examined through MTT assay. FTIR results proved oxidization of cellulose and bonding between scaffold surface and RGD. Porous microstructure having suitable size was confirmed by SEM. The results by MTT showed significant increase of viable cells on hybrid scaffold. Porous structure and high biocompatibility were the benefits of scaffold in bone tissue engineering.